A Case of Chronic Ethylene Glycol Intoxication Presenting without Classic Metabolic Derangements - Stephanie M. Toth-Manikowski; Hanni Menn-Josephy; Jasvinder Bhatia (Case Reports in Nephrology)
Acute ethylene glycol ingestion classically presents with high anion gap acidosis, elevated osmolar gap, altered mental status, and acute renal failure. However, chronic ingestion of ethylene glycol is a challenging diagnosis that can present as acute kidney injury with subtle physical findings and without the classic metabolic derangements. We present a case of chronic ethylene glycol ingestion in a patient who presented with acute kidney injury and repeated denials of an exposure history. Kidney biopsy was critical to the elucidation of the cause of his worsening renal function.